2013
DOI: 10.1371/journal.pone.0065629
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms That Determine the Internal Environment of the Developing Brain: A Transcriptomic, Functional and Ultrastructural Approach

Abstract: We provide comprehensive identification of embryonic (E15) and adult rat lateral ventricular choroid plexus transcriptome, with focus on junction-associated proteins, ionic influx transporters and channels. Additionally, these data are related to new structural and previously published permeability studies. Results reveal that most genes associated with intercellular junctions are expressed at similar levels at both ages. In total, 32 molecules known to be associated with brain barrier interfaces were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 107 publications
(152 reference statements)
5
100
0
1
Order By: Relevance
“…4a). A functional correlate has been established by permeability studies at early embryonic stages [80]. Claudin-2 expression appears to follow the developmental increase in CSF secretion capacity.…”
Section: Paracellular Barrier Properties Of the Choroid Plexus Epithementioning
confidence: 95%
See 1 more Smart Citation
“…4a). A functional correlate has been established by permeability studies at early embryonic stages [80]. Claudin-2 expression appears to follow the developmental increase in CSF secretion capacity.…”
Section: Paracellular Barrier Properties Of the Choroid Plexus Epithementioning
confidence: 95%
“…Indeed, such an approach has already been successfully applied to define new stages of lung maturation in humans. Importantly, claudin proteins are expressed at the junctions linking the epithelial cells in the nascent choroid plexus in human, and evidence of the tightness of these junctions has been provided in embryonic rodents ( [74,80], and see infra). This suggests that the barrier originates as early as the choroid plexus develops.…”
Section: Understanding Choroid Plexus Developmentmentioning
confidence: 99%
“…Vigorous choroidal blood flow, together with the activities of key transport enzymes -Na + -K + -ATPase and carbonic anhydrase -drives the CPmanufactured CSF (containing Na + , Cl − , HCO 3 − ) into the four ventricles (Lorenzo and Snodgrass, 1972). Transcriptome analysis of Na-K-ATPase isoforms and carbonic anhydrase 2 in rat CP, both integral to CSF formation, reveals that these key transport enzymes appear (mRNA) in embryonic life (Liddelow et al, 2013); and thereafter their expression is augmented postnatally as CSF formation and pressure continuously rise to the adult level. It is impressive that CP can actively secrete CSF even when a substantial hydrostatic pressure is exerted on choroidal cells, either perpendicular to the epithelium as a monolayer in a transwell in vitro or when freely suspended in the ventricles under elevated intracranial pressure in situ (as in hydrocephalus).…”
Section: Cerebrospinal Fluid Secretion By Cpmentioning
confidence: 99%
“…2D), following peripheral administration of an estrogen receptor antagonist. While we did not repeat these pharmacological studies, prior investigations have demonstrated direct actions of estrogens on ChP transcription of Ttr (11), its most highly expressed gene (3,4). …”
mentioning
confidence: 90%
“…We re-examined the top 15 differentially-expressed genes (DEGs) reported by Cho et al . (1) at 4h following contextual fear conditioning, and observed very low levels of expression in the hippocampus [see Allen Brain Atlas (2)], but noted that 11 of the genes rank among the top expressed transcripts in the choroid plexus (ChP), and together belong to the characteristic transcriptomic signature of the ChP that we (3), and others (4) have characterized.…”
mentioning
confidence: 99%